Tenses, Dates and Times - Korta, Kepa; Ponte, María (Research in Language, 2014)
This paper presents a theory of utterance content that is neutral with respect to some of the key issues in the debate about the proper semantics of tense. Elaborating on some ideas from Korta & Perry (2011), we defend a proposal according to which utterances of both temporally specific and temporally unspecific sentences have a systematic variety of contents, from utterance-bound to incremental or referential. This analysis will shed some light on the contribution of tense to what is said by an utterance.